2020
DOI: 10.1007/s10803-020-04653-7
|View full text |Cite
|
Sign up to set email alerts
|

The Self of Adolescents with Autism Spectrum Disorder or Attention Deficit Hyperactivity Disorder: A Qualitative Study

Abstract: Self-development is a central developmental issue in adolescence, there are few studies describing the experiences related to the self in adolescents with autism spectrum disorder (ASD) or attention deficit hyperactivity disorder (ADHD). We conducted semi-structural interviews with 14 adolescents with ASD and three with ADHD to describe the self. As a result of inductive continuous comparison analysis, three concepts “Interest in self and self-realization”, “Intentionality and self-transformation”, “Unrealized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…For example, when they were younger not being allowed to go on a break at the same time as the other children had created a feeling of exclusion, which led to frustration, and fighting and could affect their ability to make and keep friends. In their study Hanai et al [26] also noted that adolescents derived a sense of security by maintaining stable connections with their friends, classmates, teachers, and family members. Lam et al [27] found that friends were important for adolescents in general as friends influenced their behaviour, norms, and values.…”
Section: Plos Mental Healthmentioning
confidence: 97%
“…For example, when they were younger not being allowed to go on a break at the same time as the other children had created a feeling of exclusion, which led to frustration, and fighting and could affect their ability to make and keep friends. In their study Hanai et al [26] also noted that adolescents derived a sense of security by maintaining stable connections with their friends, classmates, teachers, and family members. Lam et al [27] found that friends were important for adolescents in general as friends influenced their behaviour, norms, and values.…”
Section: Plos Mental Healthmentioning
confidence: 97%
“…However, profound interindividual differences exist 75 . Some of them do not accept their neurodiversity (“ I hate myself who cannot do well like others” 76 ); others eventually accept it and would not like to change “ because it's the reason why I am who I am ” 74 , and they “ like being different ” 74 or are even “ proud ” of it 75 .…”
Section: The Inner Subjective Experience Of Mental Disorders In Adole...mentioning
confidence: 99%
“…Neurodiversity makes the lived world of adolescents with autistic spectrum disorders an extremely challenging place, particularly when confronted with the neurotypical world (“ This world is still a puzzle to me, like how people act and how rules are ” 73 ; “ I’m working my brain harder than anyone else” 76 ). They may feel their mind “ moving into chaos, like a messy office ” 77 .…”
Section: The Inner Subjective Experience Of Mental Disorders In Adole...mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Hanai et al (2021) focused on 'the self' in Japanese autistic participants and those with attention deficit/hyperactivity disorder (ADHD) during adolescencea period during which one's sense of self changes profoundly, especially through interpersonal interactions with others. Some of their participants reported starting to think about themselves in relation to other, non-autistic students when they were placed in a special support class.…”
Section: Introductionmentioning
confidence: 99%